Guillermo Hoyos Vásquez (1935-2013) In Memoriam - Calvo de Saavedra, Angela; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2013)
The teacher, the friend, the tireless defender of public reason, is authorized and poignant portrayal of who, like us, accompanied him on his journey. Sit tibi terra levis, William.